Desain Web Sistem Pengenalan Identitas Jemput Murid Tk Negeri Sendangmulyo Semarang Menggunakan QR Code - Farkhan Rauf Hafiidh; Nur Hakim, Fitro (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
TK Negeri Sendangmulyo Semarang is an international level state kindergarten in Semarang locates in Jalan Klipang Raya Sendangmulyo Tembalang, Semarang 50272. Student pick-up system works like student pick-up in general. Parents come to school and directly pick their sons or daughters. But under parents’ circumstance, parents may be able or unable to pick their kids. If parents unable to pick-up their kids, teachers need to know the person actually pick the students whether family member or the parents trustee. For that reason, Identity Recognition System for Kindergarten Student Pick-Up using QR Code is needed. In general, developed system use QR Code. Research method used by researcher among other data collection method such as literature study, field study by observation and interview, also previous research study. While development method in the Identity Recognition System for Kindergarten Student Pick-Up using QR Code use System Development Life Cycle coupled with Unified Modeling Language for modeling. By implementing the system, teachers may control and watch kindergarten student pick-up system. The result is new kindergarten student pick-up system where student may get picked-up if the person brings ID-Card contains QR Code with student data